Synthesize and Characterization of Pt-supported Co-ZIF for Catalytic Hydrocracking and Hydroisomerization of n-Hexadecane - Hidayati, Luthfiana Nurul; Aulia, Fauzan; Napitupulu, Sebastian Ulido; Adhyaksa, Gede Widia Pratama; Dahnum, Deliana (Bulletin of Chemical Reaction Engineering & Catalysis, 2024)
Zeolitic Imidazole Frameworks (ZIFs) are prospective porous materials as catalyst support due to their relatively large surface area, and tunability in size, structure, and porosity. Recent studies have also shown that ZIF is the best candidate for various catalytic redox reactions such as the oxidation of benzyl aromatic hydrocarbons. In this study, the synthesized Pt catalyst supported on Co-ZIF was varied by the organic ligands: imidazole, benzimidazole, and 1-(3-aminopropyl) imidazole, then followed by impregnation of Pt precursor. The catalysts were characterized its physical and chemicals properties such as Fourier Transform Infrared (FTIR), X-ray Diffraction (XRD), Scanning Electron Microscope (SEM), and Brunauer Emmet Teller (BET), Temperature-Programmed Desorption (NH3-TPD and CO2-TPD). The prepared catalysts were evaluated for catalytic hydrocracking and hydroisomerization of n-hexadecane in a 100 ml-batch reactor. GC-MS analysis presented that the Pt/ZIF catalyst with imidazole ligands has better performance than others. Hence, the optimization of n-Hexadecane conversion was carried out by the Pt/ZIF-imidazole catalyst varying the amount of metal loading, time and temperature reaction. The results showed that the reaction temperature of 350 ºC using 20 bar H2 for 4 h and the addition of 15 wt% Pt successfully achieved 90.77% conversion and produced the highest yield of isomers and alkanes, 4.04% and 35.75%, respectively. Copyright © 2024 by Authors, Published by BCREC Publishing Group. This is an open access article under the CC BY-SA License (https://creativecommons.org/licenses/by-sa/4.0).